River Polution and Restoration Towards Sustainable Water Resources Management in Malaysia - Chan, Ngai Weng; Ibrahim, Abd. Latif; Lee Abdullah, Anisah; Ghazali, Suriati (2003)
Malaysian settlement~ have historically sprung up along river banks and river estuaries. Tn many ways, rivers are sources of life, providing water supply for the people, irrigation for agriculture, as a means of transportation, a source of food in fisheries, hydro-electric power, and water use for industries. Rivers are also the habitats for riverine and aquatic flora and fauna and the river environment supports a rich biodiversity of life forms. Unfortunately, however, rivers also provide an easy conduits for the discharge of varying domestic, commercial, industrial and agricultural effluents via their natural function as drainage channels for flood mitigation. Malaysia bas developed very rapidly over the last three decades, with urbanisation increasing many folds in all the major cities and towns. Coupled with this, agriculture expansion and industrialisation have also rapidly changed the land use from one of mainly forest and food crops to one of estates (cash crops), urban, commercial and industrial centres. All the~e developments have overstressed river systems. As a result, many river basins have reached their limits of water supply an a are now susceptible to water stress and droughts. The occurrence of low flows is exacerbated when rapid development has produced great amounts of human wastes as well as wastes from all of man's activities, including agriculture, industrial, commercial and transportation wastes. This has resulted in a large number of polluted rivers, some to the extent of being not rehabilitable. Yet, many rivers can be restored and rehabilitated given the right kind of efforts. Deforestation bas also led to the opening up of large tracts of land within river basins and this has resulted in not only increased sediment loading in the river systems but also in the aggravation of floods which further pollute the waters. Currently, there have been some fragmented efforts from the authorities and the public for river restoration and rehabilitation. The Drainage and Irrigation Department has initiated a program to dean up the Kelang River, i.e. to clean the river of solid waste and silt, to improve water quality to Class III (recreational purposes without body contact) and to beautify strategic stretches of the river for recreational purposes. So far, it has had mixed results. Some stretches in the cities are showing good results as more attention has been focussed there but elsewhere the river is as dirty as ever. It is also a top-down approach that did not involve much participation from the local communities. Hence, they were often met with scepticism and resistance. Some river cleaning works were stalled mainly due to the resistance of riverine squatters who refuse to cooperate. Consequently, the whole approach to river restoration has changed. More and more, the public and water NGOs are playing a more important role. This is especially so when the community involved is the one that lives besides the river. This study demonstrates that river restoration and rehabilitation can only be successful with a combined effort between government, NGOs and the local communities working together to ensure the cleanliness of the rivers.